City of San Jose from City Hall - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic view of the City of San Jose, California, taken from San Jose City Hall; on the left, looking down Market Street; on the center right, looking down San Antonio Street. On the right of Market Street is the old San Jose Post Office and San Jose Public Library. Further up on Market Street is St. Joseph's Cathedral.